Research on a grille control scheme to enhance safety and comfort of rail vehicles - LI Yang; LIU Youmei; CHEN Yong; LIU Xiaofeng; WANG Hugao; CHEN Zhongjie (机车电传动)
In order to improve the safety and comfort level of rail vehicles, a control scheme of vehicle grille was presented. When a fire occurred in a train, the spread of flame and poison gas could be prevented and the poison gas discharge could be promoted by opening and closing the air return grille of partition door, air supply grille of driver's cab wind crossing, inlet valve of air conditioning fresh air device and exhaust valve of waste discharge device, so the life safety of passengers and drivers could be protected maximum; When the external pressure of the train fluctuated violently, while the internal space completely was isolated from the external environment, and the driver's cab was also separated from the passenger compartment, if the total pressure decompression time of driver's cab part component was greater than the total pressure decompression time of passenger compartment part component at this time under certain conditions, the fluctuation of the air pressure driver's cab could be reduced and comfort level of driver's cab could be improved, at the same time, the calculation and verification were carried out. The research provides a reference for safety and comfort design of rail vehicles.